USE OF INTERNET SERVICES IN THE ORGANIZATION OF INDEPENDENT EDUCATION - Xikmatov N. N. (Web of Journals Publishing, 2024)
The article will talk about independent education and its organization. Internet services that can be applied in the process of independent education are provided.
Keywords: credit, Independent Education, Education, Internet Services, forum.